ABO BLOOD GROUPS IN RELATION TO ISCHAEMIC HEART DISEASE - Akhund, Israr Ahmed; Akhund, Anwar Ali; Alvi, Irshad Ali; ullah, Hafeez; Ansari, Ahmed Kamal (Journal of Ayub Medical College Abbottabad, 1998)
This study was planned to see any relationship between ABO blood groups and ischaemic heart disease, by using a series of patients with IHD. Accordingly, interest attaches to our findings that the highest incidence was observed in blood group A (44%), followed by O (28%), B (22%) and AB (6%). Although majority of patients in group A were nonsmokers and non-diabetics but the incidence was observed still higher in this group. An important conclusion is reached that the individuals who have An antigen are more susceptible to develop IHD. KEY WORDS: ABO Blood Groups, Ischaemic Heart Disease.